ROOT TUBERS EXPANSION PRORAMME (RTEP) AND QUALITY OF PRODUCTS OF MICRO-SCALE CASSAVA PROCESSORS IN OYO STATE NIGERIA - OKHANKHUELE, OMONIGHO TONIA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
High unemployment and poverty rate have become alarming over the world especially in Sub-Saharan Africa. Consequently, several poverty alleviation and employment generation programmes have been implemented by Nigerian governments. Root Tubers Expansion Programme (RTEP) is one of such programmes. Past researches have been carried out on challenges and effect of RTEP’s technologies on farmers’ productivity and poverty alleviation, but no indebt research on effect of RTEP on micro-scale cassava processors’ (MSCPs) products’ quality. This research intends to close this gap by assessing the effect of RTEP on the quality of MSCPs’ products. Survey design was used for the study, and the MSCPs were selected with multistage sampling technique. Data from 151 respondents were gathered with structured questionnaire and analysed with descriptive statistic. Hypothesis was tested with t-test at 5% significant level. The level of significance of .000 respectively which were lower than the table value of 0.05 were obtained from the t-test meaning there was a significant difference in MSCPs products’ quality before and after partaking in RTEP. The paper recommends the implementation of more integrative poverty alleviation and employment generation programmes to improve the MSCPs products’ quality and make them more competitive in local and world markets.